Binational organizations of Mexican migrants in the United States - Rivera Salgado, Gaspar (Social justice, 1999)
Part of a special issue on collective identities, social problems, and movements. The writer discusses binational organizations of Mexican migrants in the U.S. and their attempts to respond to complex problems facing migrants on both sides of the U.S.-Mexico border. He locates these organizations within the context of the history of Mexican migration to the U.S. and its changing profile. He examines the experiences of federations of civic clubs from several Mexican states, known as “Hometown Associations,” that began in the 1970s and the more recent grassroots organizations of indigenous migrants. He identifies the challenges ahead for cross-border organizations as being to build upon the experiences of already existing social networks of migrants and to transcend the “local” vision to form links with other social and political sectors and internationalize the migration problem.